Regional Capacity Building on Weather Research and Forecasting Hydrological (WRF-Hydro) Modeling System for Improved Flash Flood Early Warning and Action - Amha, Yosef; Bahaga, Titike; Demissie, Teferi; Makonnen, Brook T.; Bekele, Tamirat; Solomon, Dawit (International Livestock Research Institute, 2024)
The main objective of this regional training workshop was to capacitate participants with the theoretical concept of the Weather Research and Forecasting Hydrological (WRF-Hydro) modeling system, along with practical hands-on exercises in model calibration and configuration. Hence, the five-day workshop agenda was designed to satisfy the needs of meteorologists, hydrologists, and researchers by providing both theoretical and hands-on skills related to WRFHydro modeling. Accordingly, the rationale behind WRF-Hydro as a tool against existing regional hydrological challenges was presented and discussed. This was based on a foundation of basic principles of physical hydrology to help participants learn more advanced modeling techniques. Such discussions covered an overview of WRF-Hydro applications worldwide, Linux for preparing the model environment, and in-depth WRF-Hydro modeling. Later, greater emphasis was placed on hands-on training in model execution, evaluation, and calibration to turn theoretical knowledge into practice. Participants were taken through practical exercises involving preparing model domains using the WRF Pre-processing System (WPS), pre-processing Geographic Information System (GIS) terrain data, and preparing compulsory forcing data for running WRF-Hydro simulations. The last session was used to present the case studies, share experiences, and possibly collaborate on new ideas. By the end of the training, participants had the tools and expertise to apply WRF-Hydro in their operations, particularly flood and stream flow forecasting, to support improved water resource management and enhanced climate resilience. This workshop took place from June 24—28, 2024, at the ILRI Campus in Addis Ababa, Ethiopia, and was co-organized by the IGAD Climate Prediction and Application Centre (ICPAC) through the Co-Production of Climate Services for East Africa (CONFER) project and the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA). Experts from ICPAC, Karlsruhe Institute of Technology (KIT), the University of Augsburg in Germany, the University of Calabria in Italy, and NORCE in Norway supported the training.